Flexible laminated material

JP2024527883A5Inactive Publication Date: 2025-03-14THE CHEMOURS CO FC LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024504140
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-07-30
Filing Date
2022-05-05
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing metal clad laminates used in electronic applications face challenges with high dielectric constants, high dielectric loss tangents, and poor adhesion, leading to issues such as conductive anodic filament formation and limited flexibility, which affect their performance in high-frequency applications.

Method used

A laminate article comprising a perfluorocopolymer matrix with embedded quartz cloth and a conductive cladding, where the matrix includes fluorinated and non-fluorinated perfluorocopolymers with controlled carboxyl end groups and UV-absorbing additives, allowing for low dielectric constants, low loss tangents, and strong adhesion, enabling UV drilling and flexibility.

Benefits of technology

The solution provides a laminate with improved electrical properties, reduced conductive anodic filament formation, and enhanced flexibility, suitable for high-frequency applications like 5G communication networks and automotive radar.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The laminate article includes a dielectric substrate comprising a perfluorocopolymer matrix including a fluorinated perfluorocopolymer and a non-fluorinated perfluorocopolymer, a quartz cloth embedded in the perfluorocopolymer matrix, and an additive material dispersed in the perfluorocopolymer matrix, the additive material being capable of absorbing ultraviolet light, and a conductive cladding disposed on a surface of the dielectric substrate.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] (CROSS REFERENCE TO RELATED APPLICATIONS) This application claims priority to PCT Application No. PCT / CN2021 / 109685, filed July 30, 2021, the contents of which are incorporated by reference in their entirety herein. [Background technology]

[0002] Metal clad laminates are used as printed wiring board substrates in a variety of electronic applications. Summary of the Invention [Means for solving the problem]

[0003] In a first aspect, a laminate article includes a dielectric substrate comprising a perfluorocopolymer matrix including a fluorinated perfluorocopolymer and a non-fluorinated perfluorocopolymer, a quartz cloth embedded in the perfluorocopolymer matrix, and an additive material dispersed in the perfluorocopolymer matrix, the additive material being capable of absorbing ultraviolet light, and a conductive cladding disposed on a surface of the dielectric substrate.

[0004] Implementations may include one or any combination of two or more of the following features.

[0005] The laminate article has a thickness of from 20 μm to 200 μm, such as from 30 μm to 90 μm, for example from 30 μm to 60 μm.

[0006] The dielectric substrate has a dielectric constant at 10 GHz of 2.10 to 2.50, for example, 2.10 to 2.30.

[0007] The dielectric substrate has a thermal coefficient of dielectric constant having a value of -250 to +50 ppm / °C over the temperature range of 0 to 100°C.

[0008] The dielectric substrate has a dielectric loss tangent at 10 GHz of less than 0.001, for example, 0.0006 to 0.001, for example, 0.0006 to 0.0008.

[0009] The laminated article has a planar shape defining an XY plane, and the thermal expansion coefficient of the laminated article in the XY plane is 5 to 25 ppm / °C, for example, 14 to 20 ppm / °C, for example, 16 to 22 ppm / °C.

[0010] Fluorinated perfluoro copolymers include fluorinated tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymers, and non-fluorinated perfluoro copolymers include non-fluorinated tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymers.

[0011] The perfluorocopolymer matrix comprises 50 to 90 weight percent of fluorinated perfluorocopolymer, for example 50 to 80 weight percent of perfluorocopolymer. The perfluorocopolymer matrix comprises 10 to 50 weight percent of non-fluorinated perfluorocopolymer.

[0012] The number of carboxyl end groups per million carbon atoms in the perfluorocopolymer matrix is ​​sufficient that the laminate article does not form conductive anodic filaments (CAFs).

[0013] The number of carboxyl end groups per million carbon atoms in the perfluorocopolymer matrix provides a laminate article having a peel strength between the dielectric substrate and the conductive cladding of greater than 2 lb. / inch.

[0014] The number of carboxyl end groups per million carbon atoms in the perfluorocopolymer matrix is ​​30-70.

[0015] The fluorinated perfluoro copolymer has up to 5 carboxyl end groups per million carbon atoms.

[0016] The non-fluorinated perfluoro copolymers have from 100 to 300 carboxyl end groups per million carbon atoms.

[0017] The perfluorocopolymer matrix has a melt flow rate (MFR) of 10 g / 10 min to 30 g / 10 min.

[0018] The perfluorocopolymer matrix has a solder float resistance at 288°C of at least 10 seconds, such as 60 seconds.

[0019] The quartz cloth has a basis weight of less than 50 g / m2, for example less than 25 g / m2.

[0020] The quartz cloth has a thickness of 10 μm to 30 μm.

[0021] The quartz cloth contains an aminosilane or methacrylate silane surface chemistry treatment.

[0022] The quartz cloth includes plasma-treated or corona-treated quartz cloth.

[0023] The quartz cloth is impregnated with a fluoropolymer.

[0024] The quartz cloth includes a fluoropolymer coating.

[0025] The quartz cloth is pretreated with a fluoropolymer treatment prior to incorporation into the laminate article.

[0026] The dielectric substrate comprises 5-20 volume percent quartz cloth and 80-95 volume percent perfluorocopolymer matrix.

[0027] The water contact angle of the quartz cloth is 0° to 60°.

[0028] The additive material includes inorganic particles, such as particles of cerium oxide, titanium dioxide, silicon dioxide, barium titanate, calcium titanate, or zinc oxide.

[0029] The additive material includes a thermosetting polymer.

[0030] The additive material is present in the perfluorocopolymer matrix at a volume percent of less than 2%.

[0031] The additive material is homogeneously dispersed throughout the perfluorocopolymer matrix.

[0032] The conductive cladding is disposed on two opposing surfaces of the dielectric substrate.

[0033] The conductive cladding may, for example, comprise a copper foil disposed on the surface of the dielectric substrate by a lamination process.

[0034] The conductive cladding has a thickness of less than 72 μm, for example between 5 μm and 18 μm.

[0035] The conductive cladding has a root mean square (RMS) roughness of less than 1 μm, such as less than 0.5 μm.

[0036] In a second embodiment, a printed wiring board comprises the laminate article of the first embodiment having a conductor pattern formed within the conductive cladding.

[0037] In some examples, the through holes are defined through the thickness of the laminate article and include a copper film plating the through holes.

[0038] In a third aspect, a multilayer printed wiring board comprises a multilayer laminate structure comprising a plurality of printed wiring boards according to the second aspect.

[0039] Implementations may include one or any combination of two or more of the following features.

[0040] Multilayer printed wiring boards include a thermoplastic adhesive disposed between adjacent printed wiring boards in a laminate structure.

[0041] The thermoplastic adhesive was bonded at a temperature of 0 to 200° C. below the melting point of the perfluorocopolymer matrix, for example, at a temperature of 0 to 50° C. below the melting point of the perfluorocopolymer matrix.

[0042] Multilayer printed wiring boards include a thermosetting adhesive disposed between adjacent printed wiring boards in a laminate structure.

[0043] The thermosetting adhesive was cured at a temperature of 150°C to 250°C.

[0044] A through hole is defined through at least a portion of the thickness of the multilayer printed wiring board and includes a copper film plating the through hole.

[0045] In a fourth aspect, an antenna usable in a 5G communications network includes a printed wiring board according to the second or third aspect.

[0046] In a fifth embodiment, a method of making a multilayer printed wiring board includes forming a conductor pattern in the conductive cladding of each of a plurality of laminate articles of the first embodiment to form a respective printed wiring board, and stacking the plurality of printed wiring boards to form a multilayer laminate structure.

[0047] Implementations may include one or any combination of two or more of the following features.

[0048] Laminating multiple printed wiring boards involves bonding adjacent printed wiring boards together using a thermoplastic adhesive.

[0049] The method includes bonding at a temperature between 0° C. and 200° C. below the melting point of the perfluorocopolymer matrix, for example, at a temperature between 0° C. and 50° C. below the melting point of the perfluorocopolymer matrix.

[0050] Stacking multiple printed wiring boards together involves bonding adjacent printed wiring boards together using a thermosetting adhesive.

[0051] The method involves curing the thermosetting adhesive at a temperature between 150°C and 250°C.

[0052] The method includes defining through holes through at least a portion of the thickness of the multi-layer laminate structure, for example in an ultraviolet drilling process.

[0053] In a sixth aspect, a method of making a laminate article includes forming a layered article. The layered article includes first and second polymeric films, each of which includes a perfluorocopolymer matrix including a fluorinated perfluorocopolymer and a non-fluorinated perfluorocopolymer, and an ultraviolet radiation additive, a quartz cloth disposed between the first and second polymeric films, and a conductive cladding disposed in contact with the first film. The method includes applying heat and pressure to the layered article to form the laminated article.

[0054] Implementations may include one or any combination of two or more of the following features.

[0055] Fluorinated perfluoro copolymers include fluorinated tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymers, and non-fluorinated perfluoro copolymers include non-fluorinated tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymers.

[0056] Applying heat and pressure to the layered article includes compressing the layered article within a heated platen.

[0057] Applying heat and pressure to the layered article includes processing the layered article in a roll-to-roll lamination process.

[0058] Applying heat and pressure to the layered article includes subjecting the layered article to a temperature between 10 and 30° C. above the melting point of the perfluorocopolymer matrix.

[0059] Applying heat and pressure to the layered article includes subjecting the layered article to a temperature of 300°C to 400°C.

[0060] Applying heat and pressure to the layered article may include applying a pressure of between 200 psi and 1000 psi to the layered article.

[0061] The method includes forming a first and a second film in a melt processing and extrusion process.

[0062] Forming the first and second films includes blending a fluorinated perfluoro copolymer and a non-fluorinated perfluoro copolymer.

[0063] The method includes dispersing the additive material in the fluorinated perfluoro copolymer prior to mixing the fluorinated perfluoro copolymer with the non-fluorinated perfluoro copolymer.

[0064] The method includes treating the quartz cloth with a fluoropolymer treatment.

[0065] Treating the quartz cloth with a fluoropolymer treatment includes coating the quartz cloth with a fluoropolymer coating.

[0066] Coating the quartz cloth with a fluoropolymer coating includes coating the quartz cloth in a solution coating process.

[0067] Coating the quartz cloth with a fluoropolymer coating includes depositing fluoropolymer particles on the surface of the quartz cloth.

[0068] Each polymer film includes a first layer including a fluorinated perfluoro copolymer and a non-fluorinated perfluoro copolymer, and a second layer including a non-fluorinated perfluoro copolymer, each second layer being disposed in contact with the quartz cloth, and each second layer being disposed in contact with a conductive cladding.

[0069] The details of one or more implementations are set forth in the accompanying drawings and the description below. Other features and advantages will be apparent from the description and drawings, and from the claims. [Brief description of the drawings]

[0070] [Figure 1] FIG. 1 is a diagram of a flexible metal clad laminate. [Diagram 2] FIG. 1 is a diagram of a layered structure for a flexible metal clad laminate. [Figure 3A] FIG. 1 is a diagram of a stack having a conductive anode filament. [Figure 3B] FIG. 1 is a diagram of a stack having a conductive anode filament. [Figure 4] FIG. [Diagram 5] FIG. [Figure 6] FIG. 1 is a diagram of a communications network. [Figure 7] FIG. 1 is an illustration of a roll-to-roll lamination process. [Figure 8] 1 is a flow chart of a method of making a flexible metal clad laminate. [Figure 9] 1 is a plot of the dielectric constant at 5 GHz for various flexible copper clad laminates. [Figure 10] 1 is a plot of the dielectric loss tangent at 5 GHz for various flexible copper clad laminates. [Figure 11]1 is a plot of peel strength test results for various flexible copper clad laminates. [Figure 12] 1 is a plot of wicking test results for various flexible copper clad laminates. [Figure 13] 1 is a plot of the coefficient of thermal expansion for various flexible copper clad laminates. [Figure 14] 1 is a plot of the dielectric constant at 5 GHz for various flexible copper clad laminates. [Figure 15] 1 is a plot of the dielectric loss tangent at 5 GHz for various flexible copper clad laminates. [Figure 16] 1 is a plot of thickness test results for various flexible copper clad laminates. [Figure 17] 1 is a plot of peel strength test results for various flexible copper clad laminates. [Figure 18] 1 is a plot of wicking test results for various flexible copper clad laminates. [Figure 19] 1 is a plot of the dielectric constant at 5 GHz for various flexible copper clad laminates. [Figure 20] 1 is a plot of the dielectric loss tangent at 5 GHz for various flexible copper clad laminates. [Figure 21] 1 is a plot of thickness test results for various flexible copper clad laminates. [Figure 22] 1 is a plot of peel strength test results for various flexible copper clad laminates. [Figure 23] 1 is a plot of wicking test results for various flexible copper clad laminates. [Figure 24] 1 is a plot of peel strength test results for various flexible copper clad laminates. [Diagram 25] 1 is a plot of wicking test results for various flexible copper clad laminates. [Figure 26] 1 is a plot of water contact angle measurements. [Figure 27] 1 is a plot of water contact angle measurements. [Figure 28] 1 is a plot of peel strength test results for various flexible copper clad laminates. [Figure 29] 1 is a plot of wicking test results for various flexible copper clad laminates. [Figure 30A] 1 is a plot of modeled insertion loss. [Figure 30B] 1 is a plot of modeled insertion loss. [Figure 31A] Surface roughness scan results for two copper foils. [Figure 31B] Surface roughness scan results for two copper foils. [Diagram 32] 1 is a plot of the dielectric loss tangent of blended PFA films as a function of the number of carboxyl end groups per 106 carbon atoms in the film. [Diagram 33] 1 is a plot of the dielectric tangent of a laminate as a function of the number of carboxyl end groups per 106 carbon atoms in a blended PFA film. [Diagram 34] 1 is a plot of the sharpie wicking behavior of laminates as a function of the number of carboxyl end groups per 106 carbon atoms in a blended PFA film. [Diagram 35] 1 is a plot of the copper peel strength of laminates as a function of the number of carboxyl end groups per 106 carbon atoms in blended PFA films. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0071] Described herein is a metal clad flexible laminate having low dielectric constant and low dissipation at high frequencies, e.g., 10 GHz. The flexible laminate described herein can be used in substrates for printed wiring boards in high frequency applications, such as antennas for use in 5G cellular communication networks or for use in automotive radar, among other applications. The flexible laminate described herein includes a dielectric substrate formed from a perfluorocopolymer matrix and quartz cloth embedded therein, e.g., woven quartz cloth. The perfluorocopolymer matrix includes fully fluorinated perfluorocopolymers (referred to herein as "fluorinated perfluorocopolymers") and non-fully fluorinated perfluorocopolymers (referred to herein as "non-fluorinated perfluorocopolymers"), such as fully fluorinated and non-fully fluorinated tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymers. The additive material in the dielectric substrate can absorb ultraviolet light, for example, so that the laminate can be drilled with an ultraviolet laser to form through-holes through the thickness of the laminate. The flex laminate is clad on one or both sides with a conductive cladding, such as copper foil.

[0072] 1, a metal clad flexible laminate 100 includes a dielectric substrate 102 and a conductive cladding, such as metal (e.g., copper) foils 104a, 104b (collectively referred to as conductive cladding 104), disposed on top and bottom surfaces 106a, 106b, respectively, of the dielectric substrate 102. Although the conductive cladding 104 is present on both surfaces 106a, 106b of the dielectric substrate 102 in FIG. 1, in some examples the conductive cladding is disposed on only a single surface of the dielectric substrate 102 (e.g., only on the top surface 106a).

[0073] The dielectric substrate 102 of the flexible laminate 100 includes a quartz cloth 108, such as a woven quartz cloth, embedded in a perfluorocopolymer matrix 110 including fluorinated and non-fluorinated perfluorocopolymers, such as fluorinated and non-fluorinated tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymers. As discussed further below, the perfluorocopolymer matrix 110 provides the dielectric substrate 102 with a low dielectric constant and low dissipation factor, while the quartz cloth allows the coefficient of thermal expansion (CTE) of the dielectric substrate 102 in the xy plane to be matched to the CTE of the conductive cladding 104. An additive material 112 capable of absorbing ultraviolet (UV) light, e.g., light having a wavelength between 180 nm and 400 nm, is dispersed in the perfluorocopolymer matrix 110. The presence of the UV-reactive additive material 112 allows the flex laminate 100 to be drilled by a UV laser, for example, to form circuit structures such as vias through the thickness of the flex laminate 100 .

[0074] The flexible laminate 100 is a planar structure having a thickness along the z-axis of less than about 200 μm or less than about 100 μm, for example, 20 μm to 200 μm, for example, 30 μm to 90 μm or 30 μm to 60 μm. The thickness of the dielectric substrate 102 constitutes the majority of the thickness of the flexible laminate 100. For example, the dielectric substrate 102 has a thickness along the z-axis of less than about 200 μm or less than about 100 μm, for example, 20 μm to 200 μm, for example, 30 μm to 90 μm or 30 μm to 60 μm. Each conductive cladding 104a, 104b has a thickness along the z-axis of less than about 72 μm, for example, less than about 18 μm, for example, 5 μm to 18 μm.

[0075] The dielectric substrate 102 of the flexible laminate 100 has a low dielectric constant, for example a dielectric constant at 10 GHz of less than about 2.5, for example, 2.1 to 2.5, for example, 2.1 to 2.3. The dielectric constant has a thermal coefficient with an aa value of -250 to 50 ppm / °C, for example, -100 to 50 ppm / °C or -50 to 25 ppm / °C, over a temperature range of 0 to 100°C. The dielectric substrate 102 also has a low dielectric loss tangent, for example, a dielectric loss tangent at 10 GHz of less than 0.001 or less than 0.0008, for example, 0.0002 to 0.001, for example, 0.0006 to 0.001, for example, 0.0006 to 0.0008, less than 0.0015.

[0076] The improved electrical properties of the flexible laminate 100 (e.g., low dielectric constant and low dissipation factor) allow designers to realize, for example, up to 25% or more improvement in insertion loss for a given characteristic impedance over existing flexible materials. It is believed that low levels of ferromagnetic elements (e.g., Fe, Ni, or Co) in the conductive cladding 104 (e.g., in the copper foil) can help achieve low insertion loss.

[0077] The coefficient of thermal expansion (CTE) of the dielectric substrate 102 and the CTE of the conductive cladding 104 are similar in the xy-plane of the flexible laminate 100. For example, when the conductive cladding 104 is a copper foil, the CTE of the dielectric substrate 102 in the xy-plane can be 5-25 ppm / °C, such as 16-22 ppm / °C, such as 14-20 ppm / °C. The matching of CTE values ​​between the dielectric substrate 102 and the conductive cladding 104 provides dimensional stability, e.g., less than about 0.1%, to the flexible laminate 100, such that the flexible laminate maintains its original dimensions within about 0.1% upon removal of the conductive cladding and undergoing temperature changes.

[0078] The conductive cladding 104 of the flexible laminate 100 is strongly adhered to the dielectric substrate. For example, the peel strength between the dielectric substrate 102 and the conductive cladding 104 is greater than 2 lb. / inch, such as greater than 4 lb. / inch, such as between 2-20 lb. / inch or between 4-20 lb. / inch. The flexible laminate 100 is mechanically robust to bending and can be bent through bend radii typically found in electronic devices without breaking any of the components of the flexible laminate 100. This flexibility facilitates installation of the flexible laminate 100 into a device.

[0079] The flexible laminate 100 is compatible with metallization techniques, e.g., plasma metallization, such that through holes can be drilled by a UV laser to form through the thickness of the flexible laminate 100 (e.g., along the z-axis of the flexible laminate 100). The dielectric substrate 102 of the flexible laminate 100 has a solder float resistance at 288°C of at least 5 seconds, at least 10 seconds, at least 30 seconds, or at least 60 seconds, e.g., 5-20 seconds, 10-15 seconds, 10-30 seconds, 10-60 seconds, or 30-60 seconds.

[0080] The flexible laminate 100 can be used in printed wiring boards, such as flexible printed circuit board antennas. For example, the dimensions and electrical properties of the flexible laminate 100 can make it suitable for use in high frequency applications, such as antennas for mobile devices usable on 5G communication networks, or for use in automotive radar or other high frequency applications, as discussed further below. In some examples, multiple flexible laminates 100 can themselves be stacked into a multi-layer circuit board structure. The flexible laminate is substantially void-free and resistant to the formation of conductive anode filaments, which contributes to the electrical reliability of the flexible laminate as a printed wiring board substrate.

[0081] The low dielectric constant and low dielectric loss tangent of the dielectric substrate 102 of the flexible laminate 100 are due, at least in part, to the composition of the perfluorocopolymer matrix 110. The perfluorocopolymer matrix 110 includes fluorinated perfluorocopolymers, such as fluorinated tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymers, and non-fluorinated perfluorocopolymers, such as non-fluorinated tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymers. The fluorinated perfluorocopolymers, non-fluorinated perfluorocopolymers, or both, can be linear, unbranched polymers. Fluorinated perfluorocopolymers have low or zero polarity and therefore low dielectric constant and low dielectric loss tangent. However, fluorinated perfluorocopolymers are generally non-reactive, for example, fluorinated copolymers have poor adhesion to the quartz cloth 108 and the conductive cladding 104. The non-fluorinated perfluoro copolymer has reactive end groups (e.g., carboxyl or amide end groups) that are attracted to the quartz cloth 108 and the conductive cladding 104. The presence of these reactive end groups promotes adhesion between the perfluoro copolymer matrix, the quartz cloth 108, and the conductive cladding 104.

[0082] In some instances, the perfluorinated copolymers are prepared by aqueous dispersion polymerization and, as polymerized, have a molecular weight of 10 6Per carbon atom of the fluoropolymer may contain at least about 400 reactive end groups. Most of these end groups are thermally unstable in the sense that when exposed to heat or film lamination conditions such as those encountered during extrusion and film formation, they may undergo chemical reactions such as decomposition and decarboxylation, causing the extruded polymer to discolor or to fill it with non-uniform bubbles, or both. To make the fluorinated perfluorocopolymer described herein, the polymerized perfluorocopolymer is stabilized to replace substantially all of the reactive end groups with thermally stable -CF3 end groups. An exemplary method of stabilization is exposure of the fluoropolymer to a fluorinating agent such as elemental fluorine, for example, by processes such as those disclosed in U.S. Pat. No. 4,742,122 and U.S. Pat. No. 4,743,658, the contents of which are incorporated herein by reference in their entirety.

[0083] Non-fluorinated perfluoro copolymers typically have a higher dielectric loss tangent than fluorinated perfluoro copolymers. The composition of the perfluoro copolymer matrix 110 can be tailored to achieve both a sufficiently low dielectric constant and low dielectric loss tangent for the dielectric substrate 102, as well as sufficient adhesion to the quartz cloth 108 and conductive cladding 104. For example, the composition of the perfluoro copolymer matrix 110 can be tailored to provide as much fluorinated copolymer as possible while still maintaining sufficient adhesion to the quartz cloth 108 and conductive cladding 104. A sufficiently low dielectric constant for the dielectric substrate 102 is a dielectric constant at 10 GHz of less than about 2.5, e.g., 2.1 to 2.5, e.g., 2.1 to 2.3. A sufficiently low dielectric loss tangent for the dielectric substrate 102 is a dielectric loss tangent at 10 GHz of less than 0.001, such as 0.0002-0.001, e.g., 0.0006-0.001, e.g., 0.0006-0.0008. In some examples, the sufficiency of the adhesion between the perfluorocopolymer matrix 110, the quartz cloth 108, and the conductive cladding 104 is determined by the peel strength between the dielectric substrate 102 and the conductive cladding 104. For example, the adhesion is sufficient if the peel strength is greater than 2 lb. / inch, e.g., greater than 4 lb. / inch, e.g., 2-20 lb. / inch or 4-20 lb. / inch. In some examples, the sufficiency of the adhesion between the perfluorocopolymer matrix 110, the quartz cloth 108, and the conductive cladding 104 is determined by the tendency of the flexible laminate 100 to resist the formation of conductive anode filaments (CAFs), which will be discussed further below.

[0084] In some examples, the composition of the perfluorocopolymer matrix 110 is indicated by the ratio (e.g., weight or volume ratio) of fluorinated perfluorocopolymer to non-fluorinated perfluorocopolymer. The weight percentage of fluorinated perfluorocopolymer can be 50% to 90%, such as 50% to 80%, e.g., 50%, 60%, 70%, 75%, 80%, or 90%. The weight percentage of non-fluorinated perfluorocopolymer can be 10% to 50%, e.g., 10%, 20%, 25%, 30%, 40%, or 50%.

[0085] In some examples, the composition of the perfluorocopolymer matrix 110 is indicated by the number (e.g., number concentration) of carboxyl end groups present in the perfluorocopolymer matrix 110. Non-limiting examples of such carboxyl end groups include -COF, -CONH2, -CO2CH3, and -CO2H, and are determined by the polymerization aspects, such as the selection of the polymerization medium, the initiator, the chain transfer agent, if present, and the buffer, if present. The number of carboxyl end groups per million carbon atoms present in the perfluorocopolymer matrix 100 can be 30 to 70, e.g., 35 to 65. The number of carboxyl end groups can be selected to achieve sufficient adhesion between the perfluorocopolymer matrix 110 and the quartz cloth 108 and the conductive cladding 104 while also achieving a sufficiently low dielectric constant and dissipation factor. For example, the number of carboxyl end groups can be selected to avoid the formation of CAF in the flexible laminate 100. In some examples, the composition of fluorinated and non-fluorinated perfluoro copolymers is indicated by the number (e.g., number concentration) of carboxyl end groups present in each type of perfluoro copolymer. Fluorinated perfluoro copolymers may have less than 10 carboxyl end groups per million carbon atoms, such as 5 or less, or 1 or less, or less than 1 carboxyl end group per million carbon atoms. Non-fluorinated perfluoro copolymers may have 100-300 carboxyl end groups per million carbon atoms, such as 120-280 or 150-250 carboxyl end groups per million carbon atoms. Analysis and quantification of carboxyl end groups in perfluoro copolymers can be performed by infrared spectroscopy as described in U.S. Pat. No. 3,085,083, U.S. Pat. No. 4,742,122, and U.S. Pat. No. 4,743,658, the contents of all of which are incorporated herein by reference in their entirety. The presence of the thermally stable end group -CF3 (a product of fluorination) is inferred from the absence of unstable end groups after fluorination treatment. The presence of -CF3 end groups leads to a reduction in the dielectric tangent of the perfluorocopolymer compared to other end groups.

[0086] The melt flow rate (MFR) of the fluorinated perfluorocopolymer, non-fluorinated perfluorocopolymer, or both, can also affect the adhesion between the perfluorocopolymer matrix 110, the quartz cloth 108, and the conductive cladding 104. A polymer with a high MFR flows more easily during lamination of the flexible laminate 100 than can a polymer with a lower MFR. The flow of the perfluorocopolymer matrix 110 during the lamination process (discussed in more detail below) allows the perfluorocopolymer matrix 110 to completely encapsulate the fibers of the quartz cloth 108, resulting in a dielectric substrate 102 that is substantially void-free, e.g., non-porous. The void-free dielectric substrate 102 is resistant to CAF formation. For example, the MFR of the fluorinated perfluoro copolymer can be 1 to 40 g / 10 min, for example, 2 to 15 g / 10 min, for example, 2 g / 10 min, 4 g / 10 min, 6 g / 10 min, 8 g / 10 min, 10 g / 10 min, 12 g / 10 min, 14 g / 10 min, 16 g / 10 min, 18 g / 10 min, 20 g / 10 min, 25 g / 10 min, 30 g / 10 min, 35 g / 10 min, or 40 g / 10 min. The MFR of the non-fluorinated perfluoro copolymer can be 1 to 40 g / 10 min, for example, 2 to 20 g / 10 min, for example, 2 g / 10 min, 5 g / 10 min, 10 g / 10 min, 15 g / 10 min, or 20 g / 10 min. The fluorinated and non-fluorinated perfluorocopolymers may be provided in a ratio that results in an overall MFR for the perfluorocopolymer matrix of 10 to 30 g / 10 min, e.g., 10 g / 10 min, 15 g / 10 min, 18 g / 10 min, 21 g / 10 min, 24 g / 10 min, 27 g / 10 min, or 30 g / 10 min.

[0087] Suitable materials for fluorinated tetrafluoroethylene / perfluoro(alkyl vinyl ether) perfluoro copolymers include Teflon™ perfluoroalkane (PFA) 416HP, which has an MFR of about 40 g / 10 min, or Teflon™ PFA 440HP(A / B) (The Chemours Company, Wilmington, Del.), which has an MFR of about 16 g / 10 min or 14 g / 10 min, respectively. Suitable materials for non-fluorinated tetrafluoroethylene / perfluoro(alkyl vinyl ether) include Teflon™ PFA 316, which has an MFR of about 40 g / 10 min, or Teflon™ PFA 340 (Chemours), which has an MFR of about 14 g / 10 min.

[0088] The fluorinated perfluorocopolymer, the non-fluorinated perfluorocopolymer, or both have a high melting point, such as 250° C. to 350° C., e.g., 280° C. to 320° C., 290° C. to 310° C., e.g., about 305° C. The high melting point of the fluorinated perfluorocopolymer, the non-fluorinated perfluorocopolymer, or both results in a perfluorocopolymer matrix 100 that is resistant to high temperatures and provides a dielectric substrate 102 with sufficient solder float resistance, such as a solder float resistance at 288° C. of at least 5 seconds, at least 10 seconds, at least 30 seconds, or at least 60 seconds, e.g., 5-20 seconds, 10-15 seconds, 10-30 seconds, 10-60 seconds, or 30-60 seconds, as measured according to the IPC-TM-650 test method.

[0089] The composition of the perfluorocopolymer matrix 110 may be selected to enable the dielectric substrate 102 to be compatible with plasma processing, for example, for metallization of through holes formed through the thickness of the flexible laminate 100.

[0090] Specific examples of fluorinated tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymers suitable for inclusion in the perfluorocopolymer matrix 100 include Teflon™ perfluoroalkane (PFA) 416HP with an MFR of about 40 g / 10 min or Teflon™ PFA 440HP with an MFR of about 14 g / 10 min (The Chemours Company, Wilmington, DE).Specific examples of non-fluorinated tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymers suitable for inclusion in the perfluorocopolymer matrix 100 include Teflon™ PFA 316 with an MFR of about 40 g / 10 min or Teflon™ PFA 340 with an MFR of about 14 g / 10 min (The Chemours Company).

[0091] In some examples, the perfluorocopolymer matrix 100 is formed from a single type of perfluorocopolymer having both fluorinated and reactive end groups (e.g., rather than a mixture of fluorinated and non-fluorinated perfluorocopolymers). The ratio of fluorinated to reactive end groups in the single type of perfluorocopolymer is selected to achieve both sufficient adhesion between the perfluorocopolymer matrix 110 and the quartz cloth 108, and a sufficiently low dielectric constant and loss tangent.

[0092] The presence of the woven quartz cloth 108 allows the CTE of the dielectric substrate 102 to be matched to the CTE of the metal foil 104. The woven quartz cloth 108, which is embedded in a perfluorocopolymer matrix 110, is formed from spread glass (eg, quartz) strands.

[0093] Quartz (silicon dioxide) has a lower CTE than the perfluorocopolymer matrix 110. By adjusting the ratio of perfluorocopolymer matrix 110 to woven glass cloth 108, the CTE of the dielectric substrate 102 in the xy plane can be matched to the in-plane CTE of the metal foil 104, thereby providing a flexible laminate 100 with dimensional stability. For example, the dielectric substrate 102 can include 5-20 volume percent of the woven quartz cloth 108 and 80-95 volume percent of the perfluorocopolymer matrix 110 relative to the woven glass cloth 108. The CTE of the dielectric substrate 102 in the xy plane can be 5-25 ppm / °C, e.g., 16-22 ppm / °C, e.g., 14-20 ppm / °C, thereby providing dimensional stability of less than about 0.1%. In contrast, the CTE of the perfluorocopolymer matrix 110 alone can be 100-300 ppm / °C.

[0094] Quartz has a low dielectric constant (about 3.7 at 10 GHz) and low loss (about 0.0001 at 10 GHz), which means that the dielectric substrate 102 has a low dielectric constant and low loss even with the presence of the quartz cloth embedded in the perfluorocopolymer matrix. The woven quartz cloth 108 has a thickness of less than about 30 μm, for example, between 10 μm and 30 μm, which helps to achieve a thin dielectric substrate 102. The basis weight of the quartz cloth 108 is about 50 g / m 2 Less than, for example, about 25 g / m 2 Less than, for example, 10 g / m 2 ~25g / m 2 In a specific example, the quartz cloth 108 is 22 μm thick 1027C quartz glass (Shin-Etsu Quartz Products Co., Ltd., Tokyo, Japan).

[0095] In some examples, the woven quartz cloth 108 is subjected to one or more surface treatments to improve the wetting of the fibers of the woven quartz cloth 108 by the perfluorocopolymer matrix 110, to remove residual organic matter, or to mechanically modify the surface of the fibers to enhance adhesion between the fibers of the quartz cloth 108 and the perfluorocopolymer matrix 110. The purpose of the surface treatment may be to promote substantially complete wetting of the fibers by the perfluorocopolymer such that the perfluorocopolymer completely encapsulates the quartz bundles. Sufficient encapsulation of the quartz bundles by the perfluorocopolymer and sufficient adhesion to the quartz bundles allows the dielectric substrate 102 to be substantially free of voids, e.g., non-porous, which in turn helps to prevent the formation of conductive anode filaments and the occurrence of electromigration during post-processing, e.g., during the formation of vias through the thickness of the flexible laminate 100.

[0096] The surface treatment can include a heat treatment to remove residual organic matter (e.g., residual starch) from the surface of the quartz cloth so that a clean quartz surface is exposed to the perfluoro copolymer. The surface treatment can include the addition of an adhesion promoter, such as a methacrylate silane, an amino silane, or a fluorosilane, onto the surface of the quartz cloth. The surface treatment can include a plasma or corona treatment. The surface treatment can include a treatment with a polymer coating, such as a fluoropolymer, e.g., perfluoroalkane (PFA), fluorinated ethylene propylene (FEP), or Teflon™ amorphous fluoropolymer, to form a polymer (e.g., fluoropolymer) film on the surface of the quartz cloth. For example, the quartz cloth can be immersed in a solution containing a dispersion of a fluoropolymer to form a monolayer of the fluoropolymer on the surface of the quartz cloth. The surface treatment can include a treatment with a fluorinated silane to form a layer, e.g., a monolayer, of fluorinated molecules on the surface of the quartz cloth. A combination of surface treatments can be applied, such as a heat treatment followed by a plasma or corona treatment. The surface treatment(s) applied to the quartz cloth 108 can improve the wetting of the fibers by the perfluorocopolymer matrix 110, allowing for better encapsulation of the fibers of the quartz cloth 108 by the perfluorocopolymer matrix 110 and stronger adhesion between the perfluorocopolymer matrix 110 and the fibers of the quartz cloth 108, thereby contributing to the formation of a void-free dielectric substrate 102 that is resistant to CAF formation.

[0097] The wettability of the quartz cloth can be characterized by the water contact angle (WCA). After surface treatment, the quartz cloth can have a WCA of 0° to 60°.

[0098] In some examples, particles, such as silica particles, are embedded in the perfluorocopolymer matrix 110 rather than in the quartz cloth 108. The size and surface treatment of the particles are selected to achieve a CTE that matches the metal foil 104 and to improve the wetting of the particles by the perfluorocopolymer matrix 110.

[0099] In some examples, the laminate structure can be designed to achieve good encapsulation of the quartz cloth, for example, in addition to or instead of applying a surface treatment to the quartz cloth. Referring to FIG. 2, an exemplary metal-clad flexible laminate can be fabricated by laminating a set of layers 150. The set of layers includes multiple layers of fluoropolymer film, including non-fluorinated tetrafluoroethylene / perfluoro(alkyl vinyl ether) layers 162a, 162b disposed on either side of the quartz cloth 108, and perfluorocopolymer layers 164a, 164b including fluorinated perfluorocopolymer and non-fluorinated perfluorocopolymer disposed on the outer-facing side of each non-fluorinated layer 162. Conductive cladding (such as the metal (e.g., copper) foils 104a, 104b described above) is disposed on both outer sides of the set of layers 150. When the structure shown in FIG. 2 is laminated to produce a flexible laminate (see below for further discussion of the lamination process), the non-fluorinated layer 162 encapsulates the quartz cloth 108 such that the non-fluorinated layer 162 and the perfluoro copolymer layer 164 form a matrix in which the quartz cloth 108 is embedded, e.g., forming a dielectric substrate for the flexible laminate.

[0100] Referring again to FIG. 1, the additive material 112 is dispersed, e.g., homogeneously dispersed, in the perfluorocopolymer matrix 110. The additive material 112 is a material capable of absorbing UV light such that the flexible laminate 100 can be processed by a UV drilling process, e.g., to form vias between the top and bottom surfaces 106 of the flexible laminate 100. The additive material 112 is present in the dielectric substrate 102 at a volume percentage of less than 2%, e.g., 1-2 volume percent, e.g., 1 volume%, 1.25 volume%, 1.5 volume%, or 2 volume%. The additive material 112 can be a material having a relatively low dielectric constant, e.g., a dielectric constant between 10 and 1000, such that the inclusion of the additive material 112 in the perfluorocopolymer matrix 110 does not significantly increase the dielectric constant or dissipation factor of the dielectric substrate 102. For example, the inclusion of less than 2% by volume of the additive material 112 may increase the dielectric constant of the dielectric substrate 102 by less than 10%, such as less than 5% or less than 2%.

[0101] In some examples, the additive material 112 is an inorganic particle, such as a particle of cerium oxide (CeO2), titanium dioxide (TiO2), silicon dioxide (SiO2), barium titanate (BaTiO3), calcium titanate (CaTiO3), zinc oxide (ZnO), or other suitable material. The particle may have a diameter of less than about 5 μm, less than about 2 μm, less than about 1 μm, or less than about 0.5 μm, such as between 0.1 μm and 0.5 μm. For example, smaller particles are often more effective UV light absorbers than larger particles of similar composition. In some examples, the additive material 112 is an organic (e.g., polymeric) additive, such as a low-loss thermosetting material, such as a polyimide, that is blended into the perfluorocopolymer matrix 110. In some examples, both inorganic particles and organic additives are used as additive materials.

[0102] The copper foil 104 of the flexible laminate 100 provides a platform upon which a conductive pattern can be defined, such that, for example, the flexible laminate 100 can be used as a printed wiring board. In some examples, the copper foil 104 is disposed on the surface(s) 106 of the dielectric substrate 102 by a mechanical process, such as a roll-to-roll lamination process. For example, the copper foil can be an electrodeposited copper foil or a rolled copper foil. In some examples, the copper foil 104 is deposited, e.g., electrolytically plated, onto the dielectric substrate 102.

[0103] The copper foil 104 has a thickness of less than about 72 μm, e.g., less than about 18 μm, e.g., between 10 μm and 18 μm. The copper foil 104 has a low root mean square (RMS) roughness, such as an RMS roughness of less than 1 μm, e.g., less than 0.5 μm, as measured by non-contact interferometry. The low RMS roughness of the copper foil 104 helps maintain low insertion loss of circuits made from the flexible laminate 100. In some examples, the RMS roughness of the copper foil 104 is selected to balance low insertion loss (e.g., achievable by a low RMS roughness) and good adhesion between the copper foil 104 and the dielectric substrate 102 (e.g., achievable by a higher RMS roughness). For example, as discussed above, a sufficiently high peel strength between the dielectric substrate 102 and the copper foil 104 is a peel strength that is greater than 2 lb. / inch, e.g., greater than 4 lb. / inch, e.g., between 2-20 lb. / inch or between 4-20 lb. / inch.

[0104] The copper foil 104 has a purity of at least about 99.9%. The surface chemistry of the copper foil 104 may be affected by surface treatments, such as treatment with zinc, thermal stability additives, and treatments to resist oxidation. These surface treatments may be applied to one or both surfaces of the copper foil 104. Elements such as iron and zinc have been found to be effective in increasing peel strength without significantly degrading the electrical performance of the substrate.

[0105] As discussed above, the dielectric substrate 102 of the flexible laminate 100 is substantially void-free and has sufficient adhesion between the perfluorocopolymer matrix 110 and the quartz cloth 108, which allows the flexible laminate to resist the formation of conductive anodic filaments (CAFs). CAFs are metallic filaments that form, for example, within voids or weak areas of the dielectric substrate, for example, by electromigration of metal induced by the application of an electric field. CAF formation can lead to electrical failure, for example, when the CAFs form short paths between vias through a printed wiring board. A flexible laminate can be considered free of CAF formation when it has a resistance of more than 10 Mohms after an initial 96 hour equilibration period with less than a 10-fold drop in resistance throughout the test period. The CAF test can last, for example, up to 1000 hours or more with an applied voltage of 100VDC to 1000VDC, depending on the applicable standard.

[0106] An example of CAF formation is shown in Figure 3A, which shows a hypothetical laminate 200 having a dielectric matrix 202 with glass fibers 204 embedded therein. Through holes (sometimes referred to as vias) 206 are formed through the thickness of the laminate 200 and plated with a metal 208, for example copper. Upon application of an electric field, the metal 208 anodically dissolves, migrates, and redeposits within the dielectric matrix 202, for example at the interface between the dielectric matrix 202 and the glass fibers 204, to form filaments 210 that extend between adjacent vias 206.

[0107] 3B shows another example of CAF formation in a hypothetical laminate 250 having a dielectric matrix 252 with embedded glass fibers 254 and a conductor pattern 262, e.g., a copper pattern, defined on the top, bottom, and interior surfaces of the laminate 250. Metal, e.g., copper filaments 260 form at the interface between the conductor pattern 262 and the glass fibers 254.

[0108] 1, the dielectric substrate 102 of the flexible laminate is substantially void-free and has strong adhesion between the perfluorocopolymer matrix 110 and the quartz cloth 108. This is achieved, for example, by the properties of the perfluorocopolymer (e.g., the population concentration of reactive end groups), the surface chemistry of the quartz cloth, and manufacturing parameters such as pressure and temperature (discussed below). In addition, the arrangement of the quartz cloth 108 in the perfluorocopolymer matrix 110 is such that there is substantially no contact between the fibers of the cloth and the conductive cladding 104. As a result, CAF formation in the dielectric substrate 102 is minimal, and a reliable and robust printed wiring board substrate can be used for the flexible laminate 100.

[0109] Referring to FIG. 4, a multilayer printed wiring board 300 can be formed from a plurality of the flexible laminates 100 described above. In the example of FIG. 4, the multilayer printed wiring board 300 includes two flexible laminates 100a, 100b connected by an adhesive layer 302. Vias (also referred to as through holes; not shown) can be defined through all or a portion of the thickness of the multilayer printed wiring board, for example, by UV drilling, where the UV energy is absorbed by an additive material in the dielectric substrate of the flexible laminate 100. The vias can be plated with a metal, such as a copper film. The adhesive layer 302 can be, for example, an adhesive capable of bonding at a temperature below the melting point of the perfluorocopolymer matrix of the flexible laminate 100. In some examples, the adhesive is a thermoplastic adhesive capable of bonding at a temperature between 0° C. and 50° C. below the melting point of the perfluorocopolymer matrix. In some examples, the adhesive is a thermosetting adhesive capable of bonding at temperatures between 0° C. and 200° C., for example 150° C. to 250° C., below the melting point of the perfluorocopolymer matrix.

[0110] Referring to FIG. 5, multiple (here, three) flexible laminates 100 are laminated together to form a multi-layer printed wiring board 400. The central flexible laminate 100c includes top and bottom conductive claddings. The flexible laminates 100d, 100e each include a single conductive cladding. The flexible laminates 100c, 100d are bonded to the central flexible laminate 100e by adhesive layers 402a, 402b, respectively. The adhesive layers 402a, 402b can be, for example, an adhesive capable of bonding at a temperature below the melting point of the perfluorocopolymer matrix of the flexible laminate 100. In some examples, the adhesive is a thermoplastic adhesive capable of bonding at a temperature between 0° C. and 50° C. below the melting point of the perfluorocopolymer matrix. In some examples, the adhesive is a thermosetting adhesive capable of bonding at a temperature between 0° C. and 200° C. below the melting point of the perfluorocopolymer matrix.

[0111] Vias (not shown) may be defined through all or a portion of the thickness of multilayer printed wiring board 400, for example, by UV drilling.

[0112] Printed wiring boards made from the flexible laminates 100 described herein can be used in a variety of applications, for example, high frequency applications such as high frequency communication applications. For example, referring to FIG. 6, a printed wiring board 502 including one or more flexible laminates can be used for an antenna or antenna feed for a communication device 500 (e.g., a mobile communication device) operable on a 5G communication network. For example, the flexible laminate can be useful as a substrate for a printed wiring board for a communication device antenna or antenna feed for connecting electronic components of a device located on different planes. A printed wiring board 504 including one or more flexible laminates can be used for communication network equipment such as a transmitting antenna in a tower 508 of a cellular communication network. A printed wiring board including a flexible laminate can also be used in other applications such as a camera feed in a mobile computing device.

[0113] The flexible laminate described herein can be manufactured by a lamination process. Referring to FIG. 7, in one example, a quartz cloth 108 is disposed between two perfluorocopolymer films 120a, 120b. Each perfluorocopolymer film 120a, 120b has a thickness of 10 μm to 50 μm, for example, 20 μm to 30 μm. Conductive claddings 104a, 104b are disposed on the perfluorocopolymer films 120a, 120b, respectively. For example, the conductive cladding 104 is an electrodeposited copper foil or a rolled annealed copper foil. Each conductive cladding 104a, 104b has a thickness of less than about 72 μm, for example, less than about 18 μm, for example, 10 μm to 18 μm.

[0114] The layers of material 104, 108, 120 are heated and compressed to solidify the layers of material, thereby forming the flexible laminate 100. In some examples, the quartz cloth 108 and the two perfluoro copolymer films 120a, 120b are laminated to form a dielectric substrate, and a conductive cladding (e.g., copper foil) is electrodeposited onto the dielectric substrate in a second processing step.

[0115] The lamination process parameters (e.g., temperature, time, and pressure) are selected to achieve a target viscosity of the perfluorocopolymer that allows it to flow, thereby wetting and encapsulating the glass bundles of the quartz cloth 108, and allowing good adhesion between the perfluorocopolymer and the conductive cladding 104. For example, the process parameters are selected so that the perfluorocopolymer reaches a zero shear viscosity of 2000 Pa-s to 5000 Pa-s at 330°C. The temperature can be above the melting point of the perfluorocopolymer, e.g., 10°C to 30°C higher than the melting point of the perfluorocopolymer. For example, the temperature can be 300°C to 400°C, e.g., 320°C to 330°C, e.g., 300°C, 320°C, 340°C, 360°C, 380°C, or 400°C. The temperature ramp rate can be 1-5°C / min, e.g., 1°C / min, 2°C / min, 3°C / min, 4°C / min, or °C / min. The pressure applied to the layer of material can be 100 psi to 1000 psi, e.g., 200 psi to 1000 psi, or 600 psi to 1000 psi. The residence time (e.g., for a static lamination process) can be 30 minutes to 120 minutes, e.g., 30 minutes, 60 minutes, 90 minutes, or 120 minutes.

[0116] 7 shows an isopressure roll-to-roll lamination process using a set of rollers 600. In some examples, the roll-to-roll lamination process is an isovolume gap controlled lamination process. In some examples, the lamination process is a static lamination process in which layers of material are pressed between heated platens.

[0117] The perfluorocopolymer film 120 is formed, for example, by melt processing and extrusion. In some examples, the additive material is mixed into the molten fluorinated perfluorocopolymer, and the mixture of the fluorinated copolymer and the additive material is mixed with the molten non-fluorinated perfluorocopolymer. In some examples, the additive material is mixed into the molten non-fluorinated perfluorocopolymer, and the mixture of the non-fluorinated perfluorocopolymer and the additive material is mixed with the molten fluorinated perfluorocopolymer. The resulting perfluorocopolymer mixture is extruded to form the perfluorocopolymer film. Mixing the additive material with the non-fluorinated perfluorocopolymer helps to integrate and distribute the additive material throughout the perfluorocopolymer film.

[0118] FIG. 8 is a flow chart of an exemplary process for making a flexible laminate 100. An additive material capable of absorbing ultraviolet light is dispersed (700) in a non-fluorinated perfluoro copolymer, such as a non-fluorinated tetrafluoroethylene / perfluoro(alkyl vinyl ether) perfluoro copolymer. The additive material is, for example, cerium oxide, titanium dioxide, silicon dioxide, barium titanate, calcium titanate, or zinc oxide particles; or a polymer additive, such as a polyimide. The non-fluorinated perfluoro copolymer with the dispersed additive material is mixed (702) with a fluorinated perfluoro copolymer, such as a fluorinated tetrafluoroethylene / perfluoro(alkyl vinyl ether) perfluoro copolymer, to form a perfluoro copolymer mixture. The perfluoro copolymer mixture is melt processed and extruded to form a perfluoro copolymer film (704).

[0119] The woven quartz cloth is exposed to a surface treatment, such as a heat treatment, a corona or plasma treatment, or the formation of a coating on the surface of the fibers of the quartz cloth (706). A copper foil, e.g., an electrodeposited copper foil or a rolled annealed copper foil, is also exposed to a surface treatment, such as a heat treatment, a corona or plasma treatment, or the deposition of an adhesion promoter or thermal stability additive (708).

[0120] A layered stack of materials is formed (710) including a treated quartz cloth disposed between two perfluoro copolymer films, with treated conductive cladding on both the top and bottom of the stack. The layered stack of materials is laminated (712) by application of heat and pressure, for example, in a static lamination process or a roll-to-roll lamination process, to form a flexible laminate. EXAMPLES

[0121] The following polymers and polymer dispersions are used in these examples.

[0122] PFA1: Teflon™ PFA 440HP(A / B) (Chemours), a high purity fluorinated perfluoroalkoxy (PFA) melt processable resin with an MFR of 16 g / 10 min (for “A”) and 14 g / 10 min (for “B”).

[0123] PFA2: Teflon™ PFA 340 (Chemours), a general purpose non-fluorinated PFA melt processable resin with an MFR of 14 g / 10 min.

[0124] PFA3: Teflon™ PFA 416HP (Chemours), a high purity fluorinated PFA melt processable resin with an MFR of 40 g / 10 min.

[0125] PFA-Dispersion 1: Teflon® PFA 335D (Chemours), which is an off-white aqueous PFA dispersion stabilized with a non-ionic surfactant and has a MFR of approximately 2 g / 10 min.

[0126] PFA-Dispersion 2: Terpolymer of tetrafluoroethylene (TFE), perfluoro(ethyl vinyl ether) (PEVE), and allyl glycidyl ether (AGE). MFR of 12 g / 10 min, melting point of 244° C., PEVE content of 15 wt. %, and allyl glycidyl ether content of 0.1 wt. %. The preparation of such a terpolymer is described in U.S. Patent Application Publication No. 2010 / 0036053(A1), e.g., Example 4, the contents of which are incorporated herein by reference in their entirety.

[0127] PFA-Dispersion 3: An off-white aqueous dispersion of Teflon™ PFA 940HP Plus (Chemours), stabilized with a non-ionic surfactant and having a MFR of approximately 16 g / 10 min.

[0128] Example 1: Characterization of flexible copper clad laminates Various types of PFA films were combined with 1027C-04 quartz cloth from Shin-Etsu and 12 μm thick BHFX-P92C-HG rolled copper foil from JX Nippon Mining & Metals Corporation (Tokyo, Japan) to form flexible copper clad laminates. PFA films were extruded from PFA1 and / or PFA2 polymers manufactured by Chemours. These grades were blended to achieve the desired ratio of fluorinated to non-fluorinated perfluoro copolymer. In some cases, cerium oxide (Sigma Aldrich, St. Louis, MO) was added to evaluate the UV absorption properties of the composites. The materials were laminated in a hot oil vacuum press at a peak temperature of 320° C. and a pressure of 200 psi. Testing was performed according to the procedures outlined in Table 1.

[0129] [Table 1] Details of the experimental setup, including the materials and process conditions used, are shown in Tables 2A and 2B. The five values ​​in the "Construction" column refer to the thickness of the copper cladding on each side of the laminate (in this example, 12 μm), the thickness of the perfluorocopolymer film used to create the laminate (in this example, 25 μm; constructed from two layers of 12.5 μm PFA film), and the type of glass cloth (in this example, 1027 glass). Prior to testing, samples were equilibrated at 23° C. and 50% relative humidity for 24 hours.

[0130] [Table 2]

[0131] [Table 3]

[0132] Data from the experiments detailed in Tables 2A-2B are shown in Table 3 and Figures 9-12. Specifically, Figures 9 and 10 show the dielectric constant and dissipation factor results at 5 GHz, respectively. Figure 11 shows the machine direction (MD) peel strength test results. Figure 12 shows the results from the Sharpie wicking test.

[0133] In the Sharpie wicking test, a hole is formed in a flexible laminate, a Sharpie permanent marker is rubbed around the edge of the hole, and the hole is washed with isopropanol to remove excess ink. The radial distance away from the edge of the hole to which the ink has wicked is measured. Without being bound by theory, it is believed that this wicking test serves as an indication of adhesion between the fibers of the quartz cloth and the perfluorocopolymer matrix. Poor adhesion or poor encapsulation leaves voids into which the ink can wick, resulting in a longer travel distance. In contrast, a substrate with good adhesion and good encapsulation will show a low wicking distance.

[0134] [Table 4]

[0135] These results show that films containing blends of carboxylated end groups achieve higher copper peel strength values ​​at the expense of electrical performance (dielectric loss tangent). These results also show the importance of carboxylated end groups to achieve sufficiently low and / or zero sharpie wicking results, which is a key indicator of glass flux penetration efficiency.

[0136] Example 2: Characterization of flexible copper clad laminates Various types of PFA films were combined with 1027C-04 quartz cloth from Shin-Etsu and 18 μm thick C110 CopperBond rolled copper foil from Wieland (Louisville, KY) to form flexible copper clad laminates. PFA films were extruded from PFA1 (fluorinated PFA) and / or PFA2 (non-fluorinated PFA) grades manufactured by Chemours. These grades were blended to achieve the desired ratio of fluorinated to non-fluorinated perfluoro copolymer. In some cases, cerium oxide (Sigma Aldrich) or titanium dioxide (Chemours) was added to evaluate the UV absorption properties of the composites. The materials were laminated in a hot oil vacuum press at a peak temperature of 320° C. and a pressure of 200 psi with a 60 minute dwell time, 1 atmosphere vacuum, and a 2° C. / min ramp rate. Testing was performed according to the procedure previously outlined in Table 1. Details of the experimental setup, including the materials used in the two sets of experiments, are shown in Table 4.

[0137] [Table 5]

[0138] The data from these two sets of experiments are shown in Table 5 and Figure 13, which show the machine direction CTE (MD CTE) test results. The cross direction CTE (CMD CTE) was also measured. These results again show that the films containing the blend of carboxylated end groups achieve higher peel strength values ​​at the expense of electrical performance (loss tangent). These results also again show the importance of carboxylated end groups to achieve sufficiently low and / or zero sharpie wicking results, which is a key indicator of glass bundle penetration efficiency. Finally, these results show that a film thickness of 25 μm in combination with 1027C-04 quartz cloth achieves CTE results approaching 17 ppm / °C.

[0139] [Table 6]

[0140] [Table 7]

[0141] Example 3: Characterization of flexible copper clad laminates Perfluorinated extruded films of PFA1 polymer were combined with 1027C-04 quartz cloth from Shin-Etsu and 18 μm thick C110 CopperBond rolled copper foil from Wieland (Louisville, KY) to form flexible copper clad laminates. The materials were laminated in a continuous isostatic double belt press at a peak temperature of 320° C. and various pressures up to 80 bar. Testing was performed according to the procedure previously outlined in Table 1. Details of the experimental setup, including materials and process conditions used, are shown in Tables 6A and 6B.

[0142] [Table 8]

[0143] [Table 9] The data from these experiments are shown in Tables 7A and 7B and Figures 14-18. Specifically, Figures 14 and 15 show the dielectric constant and dissipation factor results, respectively, at 5 GHz. Figure 16 shows the thickness test results, Figure 17 shows the peel strength test results, and Figure 18 shows the results from the Sharpie wicking test. These results demonstrate that films containing very low levels of carboxylated end groups achieve very poor glass flux penetration (wicking) and very low levels of copper adhesion to the dielectric.

[0144] [Table 10]

[0145] [Table 11]

[0146] Example 4: Characterization of flexible copper clad laminates Various types of PFA films were combined with 1027C-04 quartz cloth from Shin-Etsu and 12 μm thick BHFX-P92C-HG rolled copper foil from JX Nippon to form flexible copper clad laminates. PFA films were extruded from PFA1 (fluorinated PFA), PFA3 (fluorinated PFA), or PFA2 (non-fluorinated PFA) grades manufactured by Chemours. These grades were blended to achieve the desired ratio of fluorinated to non-fluorinated perfluoro copolymer. In some cases, cerium oxide (Sigma Aldrich) or titanium dioxide (Chemours) were added to evaluate the UV absorption properties of the composites. The materials were laminated in a hot oil vacuum press at a peak temperature of 320° C. and a pressure of 200 psi with a dwell time of 60 minutes, a vacuum of 1 atmosphere, and a ramp rate of 2° C. / min. Testing was performed according to the procedure previously outlined in Table 1. Details of the experimental setup, including the materials used, are given in Table 8.

[0147] [Table 12]

[0148] The data from these experiments are shown in Table 9 and Figures 19-23. Specifically, Figures 19 and 20 show the dielectric constant and dissipation factor results at 5 GHz, respectively. Figure 21 shows the results of the thickness test, Figure 22 shows the results of the peel strength test, and Figure 23 shows the results from the Sharpie wicking test. Estimated squeeze-out is measured by measuring the distance the film flows from the edge of the laminate as it is squeezed out.

[0149] [Table 13]

[0150] These results demonstrate the strong effect of the presence of filler on peel strength and wetting of the glass bundle (sharpie wicking). These experiments show that a higher MFR fluorinated resin (PFA3 (fluorinated) grade, MFR=40) when combined with carboxylated end groups improves glass wetting and adhesion to the copper foil. These results also show that R101 titania particles (Chemours) were preferred over R103 titania particles (Chemours) based on both dissipation factor and wicking.

[0151] Example 5: Characterization of flexible copper clad laminates Blended PFA films with resin matrix compositions of 75 wt% 416 (fluorinated) and 25 wt% 340 (non-fluorinated) grades and a filler loading of 1.25 vol% R101 titania (Chemours) were combined with Spread 106 electronic grade greige glass cloth from JPS Composite Materials (Anderson, SC) and 12 μm thick BHFX-P92C-HG rolled copper foil from JX Nippon to form flexible copper clad laminates. In some cases, the glass cloth was heat treated (HT106SE) prior to lamination to pyrolyze and remove residual starch sizing on the cloth. Heat treatment of the cloth was performed at 700° F. for 30 minutes in a convection oven. The 106SE and HT106SE cloths were also coated prior to use with thin layers (approximately 1-5 gsm) of various commercial and experimental PFA materials from Chemours to determine the effect of glass surface coating on resin wetting ability and interfacial adhesion. One configuration was made using 1027C-04 quartz from Shin-Etsu as a control. The materials were laminated in a hot oil vacuum press at a peak temperature of 320°C and 600 psi pressure with a 60 minute dwell time, 1 atmosphere vacuum, and a 2°C / min ramp rate. Testing was performed according to the procedure outlined above in Table 1. Details of the experimental configuration, including materials and process conditions used, are provided in Table 10.

[0152] [Table 14]

[0153] The data from this experiment is shown in Table 11 and Figures 24 and 25, which show the peel strength test results and Sharpie wicking results, respectively. This experiment demonstrated an overall improvement in adhesion to both the copper foil and glass interfaces, as evidenced by higher peel strength numbers and overall lower sharpie wicking results.

[0154] [Table 15]

[0155] Example 6: Characterization of water contact angles The effect of surface treatments on various polymer films and reinforcements was studied. Water contact angle measurements were performed using a VCA Optima goniometer (AST Products, Billerica, MA) with edge detection and angle analysis software to aid in interpretation. Atmospheric corona treatments were performed using a laboratory treatment machine from Electro-Technic Products Inc. (Chicago, IL). Plasma treatments using air as the gas medium were performed using an Atto low pressure plasma system from Diener Electronic GmbH & Co. (Ebhausen, Germany). The surfaces studied were glass, PFA1 PFA film, PFA1 / PFA2 blend PFA film at 50 wt% of each component, 1027C-04 quartz cloth from Shin-Etsu, 1017C-02 quartz cloth from Shin-Etsu, and Spread 106 greige cloth from JPS Composite Materials. The results of these treatments are shown in Figures 26 and 27. Specifically, Figure 26 shows water contact angle measurements for glass and PFA films before and after plasma and corona treatment. Figure 27 shows water contact angle measurements for quartz and glass fabrics before and after plasma and corona treatment. A clear and significant improvement in the wetting ability of the glass reinforcement was demonstrated, while the PFA film showed some improvement as well.

[0156] Example 7: Characterization of flexible copper clad laminates Blended PFA films having a resin matrix composition of 75 wt% 416 (fluorinated) and 25 wt% 340 (non-fluorinated) grades, and a filler loading of 1.25 vol% R101 titania (Chemours) were combined with various glass cloth types and 12 μm thick BHFX-P92C-HG rolled copper foil from JX Nippon to form flexible copper clad laminates. The glass cloths used are described in Table 12 below.

[0157] [Table 16]

[0158] Heat treatment of the fabric was carried out in a convection oven at 700°F for 30 minutes. Atmospheric corona treatment was carried out using a laboratory processor from Electro-Technic Products. The materials were laminated in a hot oil vacuum press at a peak temperature of 320°C and a pressure of 600 psi with a 60 minute dwell time, 1 atmosphere vacuum, and a ramp rate of 2°C / min. Testing was carried out according to the procedure previously outlined in Table 1. Details of the experimental setup, including the materials used, are shown in Table 13.

[0159] [Table 17]

[0160] The data from this experiment is shown in Table 14 and Figures 28 and 29, which show the peel strength and Sharpie wicking results, respectively. This experiment demonstrated an improvement to the glass interface, as evidenced by adequate adhesion to the copper foil and overall lower sharpie wicking results. Specifically, the 1017C-02 and HTC1027C-04+340 samples showed significantly improved wicking results.

[0161] [Table 18]

[0162] Example 8: Insertion Loss Characterization Insertion loss was modeled for the flexible laminate 100 described above with a 50 μm thick dielectric substrate, as well as other commercially available laminate materials including polyimide and fluoropolymer (PI-FP), Liquid Crystal Polymer (LCP), and Polyimide (PI). Figures 30A and 30B show the modeled insertion loss for the flexible laminate (marked "G2") and other laminate materials. These plots show the increased insertion loss that can be achieved by the electrical properties of the dielectric substrate 102 of the flexible laminate 100.

[0163] Example 9: Elemental and Roughness Characterization of Copper Foil The copper foils were analyzed using Energy Dispersive X-Ray Analysis (EDX). The two copper foils analyzed were 12 μm BHFX-P92C-HG from JX Nippon and 18 μm BF-NN-HT from Circuit Foil Luxembourg (Wiltz, Luxembourg). The EDX results are shown in Tables 15 and 16. Essentially, the copper was found to have the expected surface treatment that enhances thermal stability (Zn). It is generally understood that the presence of very low levels of low ferromagnetic elements (e.g., Fe, Ni, Co) allows low insertion loss to be achieved. These results show that both copper foils characterized contain low ferromagnetic levels.

[0164] [Table 19]

[0165] [Table 20]

[0166] The copper foils were also analyzed using a Bruker ContourGT white light interferometer to characterize their surface roughness. Figures 31A and 31B show representative three-dimensional (3D) results at 50x magnification of roughness scans for BHFX-P92C-HG and BF-NN-HT copper foils, respectively. The results of multiple surface roughness scans are presented in Table 17. Supplier A is Circuit Foils Luxembourg, Supplier B is Wieland, and Supplier C is JX Nippon. In Table 17, Sa is the arithmetic mean height, Sku is the kurtosis, Sp is the maximum peak height, Sq is the root mean square peak height, Ssk is the skewness, Sv is the maximum pit height, and Sz is the maximum height.

[0167] [Table 21]

[0168] Example 10: Effect of End Group Content on Copper Clad Laminates The effect of end group content on copper clad laminate properties was evaluated by preparing PFA1 (fluorinated PFA) and PFA2 (non-fluorinated PFA) resins in combination with R101 titania (Chemours) at various ratios of PFA2 to PFA1. Approximately 70 grams of the resin mixture was dry blended and then fed into a Rheometer Services Inc. (Wall, NJ) System 10 batch mixer equipped with a 60 cc volume mixing bowl containing a roller blade. The blend was mixed at 150 rpm and 350°C for 10 minutes to disperse the components. The mixture was then removed from the bowl and then pressed into plaques at 350°C that were approximately 100 mm x 100 mm by approximately 0.20 mm thick for use in electrical testing and subsequent lamination. The electrical properties of the pressed films, including Dk and Df at 10 GHz, were tested and found to have the electrical properties shown in Table 18.

[0169] [Table 22]

[0170] As expected, the dielectric constant (Dk) remained fairly consistent with PFA2 loading, and the dissipation factor (Df) increased linearly with increasing concentration of PFA2 in the blends.

[0171] 10 About Selective Blending 6 Measurements were also performed to determine the total number of carboxyl end groups per carbon atom, and the results are shown in Table 19.

[0172] [Table 23]

[0173] As observed in the dielectric loss data, 10 6 The number of carboxyl end groups per carbon atom increased approximately linearly with increasing concentration of PFA2 in the PFA blends.

[0174] Figure 32 shows the 10 6 1 is a plot of the measured dielectric loss tangent (Df) as a function of the number of carboxyl end groups per carbon atom. As shown in this figure, the level of carboxyl end groups in the blended PFA film is directly related to the electrical properties of the film.

[0175] These blended PFA films were combined with 2116C-04 quartz cloth (Shin-Etsu) and 12 μm BHFX-P92C-HG copper foil (JX Nippon Mining & Metals Corporation). Both the copper foil and quartz cloth were provided as 12 inch by 12 inch panels, and the PFA film was provided as a 4 inch by 4 inch panel. The build materials were laminated in an electrically heated press (PHI, City of Industry, CA) at 320° C. and 600 psi with a 60 minute dwell time to form copper clad laminates. Experimental details are shown in Tables 20A and 20B.

[0176] [Table 24]

[0177] [Table 25]

[0178] The laminated materials were tested for a variety of properties. The results are shown in Tables 21A and 21B. Etching visual inspection is a qualitative characterization of the sample's ability to lie flat and smooth on a surface.

[0179] [Table 26]

[0180] [Table 27]

[0181] Figure 33 shows the 10 6 FIG. 34 is a plot of the dielectric tangent of the laminate as a function of the total number of carboxyl end groups per carbon atom, showing a good correlation between the dielectric tangent and the number of end groups. 6 Figure 35 is a plot of the sharpie wicking of the laminate as a function of the total number of carboxyl end groups per carbon atom, again showing a good correlation between increasing carboxyl end groups and decreasing sharpie wicking. These results show that as the number of carboxyl end groups in the PFA blend increases, the glass flux penetration efficiency (as shown by the lower sharpie wicking results) improves at the expense of electrical performance (dissipation factor). Figure 35 shows that the sharpie wicking of the laminate is improved at 10 6 1 is a plot of the copper peel strength of laminates as a function of the total number of carboxyl end groups per carbon atom. These data suggest a relationship between these two parameters.

[0182] Example 11: Sharpie Wicking Behavior of Commercially Available Laminates The Sharpie wicking test results for a laminate predict the performance of the laminate under CAF testing. To demonstrate this correlation, commercially available materials known to have good CAF resistance were subjected to the sharpie wicking test. The results of these tests are shown in Table 22. These results show that a sharpie wicking result of less than 0.5 mm corresponds to a material with good CAF resistance.

[0183] [Table 28]

[0184] Specific embodiments of the subject matter have been described. Other embodiments are within the scope of the following claims. For example, the actions recited in the claims can be performed in a different order and still achieve desirable results. As an example, the processes depicted in the accompanying figures do not necessarily require the particular order shown, or sequential order, to achieve desirable results. In certain implementations, concurrent operations and parallel processing may be advantageous.

Claims

1. 1. A laminate article comprising: A dielectric substrate, a perfluorocopolymer matrix comprising a fluorinated perfluorocopolymer and a non-fluorinated perfluorocopolymer; a quartz cloth embedded in the perfluorocopolymer matrix; a dielectric substrate including an additive material dispersed in the perfluorocopolymer matrix, the additive material being capable of absorbing ultraviolet light; a conductive cladding disposed on a surface of the dielectric substrate.

2. The laminate article of claim 1, wherein the laminate article has a thickness of from 20 μm to 200 μm.

3. The laminate article of claim 2, wherein the thickness of the laminate article is from 30 μm to 90 μm.

4. The laminate article of claim 3, wherein the thickness of the laminate article is from 30 μm to 60 μm.

5. The laminate article of claim 1, wherein the dielectric substrate has a dielectric constant at 10 GHz of 2.10 to 2.

50.

6. The laminate article of claim 5, wherein the dielectric constant of the dielectric substrate is between 2.10 and 2.

30.

7. The laminate article of claim 1, wherein said dielectric substrate has a thermal coefficient of dielectric constant having a value of -250 to +50 ppm / °C over the temperature range of 0 to 100°C.

8. 10. The laminate article of claim 1, wherein the dielectric substrate has a dissipation factor at 10 GHz of less than 0.

001.

9. The laminate article of claim 8, wherein the dielectric substrate has a dissipation factor at 10 GHz of 0.0006 to 0.

001.

10. The laminate article of claim 9, wherein the dielectric loss tangent of the dielectric substrate at 10 GHz is between 0.0006 and 0.0008.

11. 10. The laminate article of claim 1, wherein said laminate article has a planar shape defining an XY plane, and wherein said laminate article has a coefficient of thermal expansion in said XY plane of 5 to 25 ppm / °C.

12. The laminate article of claim 11, wherein the coefficient of thermal expansion of the laminate article in the XY plane is between 14 and 20 ppm / °C.

13. The laminate article of claim 11, wherein the coefficient of thermal expansion of the laminate article in the XY plane is between 16 and 22 ppm / °C.

14. 2. The laminate article of claim 1, wherein the fluorinated perfluoro copolymer comprises a fluorinated tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymer and the non-fluorinated perfluoro copolymer comprises a non-fluorinated tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymer.

15. The laminate article of claim 1, wherein said perfluorocopolymer matrix comprises 50 to 90 weight percent of said fluorinated perfluorocopolymer.

16. The laminate article of claim 15, wherein said perfluorocopolymer matrix comprises 10 to 50 weight percent of said non-fluorinated perfluorocopolymer.

17. 10. The laminate article of claim 1, wherein the number of carboxyl end groups per million carbon atoms in the perfluorocopolymer matrix is ​​sufficient such that the laminate article does not form conductive anode filaments (CAF).

18. 2. The laminate article of claim 1, wherein the number of carboxyl end groups per million carbon atoms in the perfluorocopolymer matrix provides the laminate article with a peel strength between the dielectric substrate and the conductive cladding greater than 2 lb / inch.

19. 2. The laminate article of claim 1, wherein the number of carboxyl end groups per million carbon atoms in the perfluorocopolymer matrix is ​​between 30 and 70.

20. 10. The laminate article of claim 1, wherein said fluorinated perfluoro copolymer has up to 5 carboxyl end groups per million carbon atoms.

21. The laminate article of claim 1, wherein said non-fluorinated perfluoro copolymer has from 100 to 300 carboxyl end groups per million carbon atoms.

22. The laminate article of claim 1, wherein the perfluorocopolymer matrix has a melt flow rate (MFR) of 10 g / 10 min to 30 g / 10 min.

23. 10. The laminate article of claim 1, wherein the perfluorocopolymer matrix has a solder float resistance of at least 10 seconds at 288°C.

24. The quartz cloth is 50 g / m 2 The laminate article of claim 1 having a basis weight of less than 100 g / m.

25. The basis weight of the quartz cloth is 25 g / m 2 25. The laminate article of claim 24, wherein said laminate article has a thickness of less than 1 / 2 mm.

26. The laminate article of claim 1, wherein the quartz cloth has a thickness of from 10 μm to 30 μm.

27. The laminate article of claim 1 , wherein the quartz cloth comprises an aminosilane or methacrylate silane surface chemistry treatment.

28. The laminate article of claim 1 , wherein the quartz cloth comprises a plasma-treated or corona-treated quartz cloth.

29. The laminate article of claim 1 , wherein the quartz cloth is impregnated with a fluoropolymer.

30. The laminate article of claim 1 , wherein the quartz cloth comprises a fluoropolymer coating.

31. The laminate article of claim 1 , wherein the quartz cloth is pretreated with a fluoropolymer treatment prior to incorporation into the laminate article.

32. The laminate article of claim 1, wherein said dielectric substrate comprises 5 to 20 volume percent of said quartz cloth and 80 to 95 volume percent of said perfluorocopolymer matrix.

33. 10. The laminate article of claim 1, wherein the quartz cloth has a water contact angle of from 0° to 60°.

34. The laminate article of claim 1 , wherein the additive material comprises inorganic particles.

35. 35. The laminate article of claim 34, wherein the inorganic particles comprise particles of cerium oxide, titanium dioxide, silicon dioxide, barium titanate, calcium titanate, or zinc oxide.

36. The laminate article of claim 1 , wherein the additive material comprises a thermosetting polymer.

37. 10. The laminate article of claim 1, wherein the additive material is present in the perfluorocopolymer matrix at a volume percent of less than 2%.

38. The laminate article of claim 1 , wherein said additive material is homogeneously dispersed throughout said perfluorocopolymer matrix.

39. The laminate article of claim 1 , wherein the conductive cladding is disposed on two opposing surfaces of the dielectric substrate.

40. The laminate article of claim 1 , wherein the conductive cladding comprises copper foil.

41. 41. The laminate article of claim 40, wherein the copper foil is disposed on the surface of the dielectric substrate by a lamination process.

42. The laminate article of claim 1 , wherein the conductive cladding has a thickness of less than 72 μm.

43. The laminate article of claim 42, wherein the thickness of the conductive cladding is from 5 μm to 18 μm.

44. The laminate article of claim 1 , wherein the conductive cladding has a root mean square (RMS) roughness of less than 1 μm.

45. 45. The laminate article of claim 44, wherein the RMS roughness of the conductive cladding is less than 0.5 μm.

46. A printed wiring board, The laminate article of claim 1, A printed wiring board having a conductor pattern formed within the conductive cladding.

47. 47. The printed wiring board of claim 46, wherein through holes are defined through a thickness of the laminate article and include a copper film plating the through holes.

48. 47. A multilayer printed wiring board comprising a multilayer laminate structure comprising a plurality of the printed wiring boards of claim 46.

49. 49. The multilayer printed wiring board of claim 48 including a thermoplastic adhesive disposed between adjacent printed wiring boards in said laminate structure.

50. 50. The multilayer printed wiring board of claim 49, wherein the thermoplastic adhesive is bonded at a temperature 0 to 200° C. below the melting point of the perfluorocopolymer matrix.

51. 51. The multilayer printed wiring board of claim 50, wherein the thermoplastic adhesive is bonded at a temperature 0 to 50° C. below the melting point of the perfluorocopolymer matrix.

52. 49. The multilayer printed wiring board of claim 48 including a thermosetting adhesive disposed between adjacent printed wiring boards in said laminate structure.

53. 53. The multilayer printed wiring board of claim 52, wherein the thermosetting adhesive is cured at a temperature of 150°C to 250°C.

54. 49. The multilayer printed wiring board of claim 48, wherein through holes are defined through at least a portion of said thickness of said multilayer printed wiring board and include a copper film plating said through holes.

55. An antenna usable in a 5G communications network, 49. An antenna comprising the printed wiring board of claim 48.

56. 1. A method for making a multilayer printed wiring board, the method comprising: forming a conductor pattern within the conductive cladding of each of a plurality of laminate articles according to claim 1 to form a respective printed wiring board; and stacking a plurality of printed wiring boards to form a multi-layer laminate structure.

57. 57. The method of claim 56, wherein stacking the plurality of printed wiring boards comprises adhering adjacent printed wiring boards using a thermoplastic adhesive.

58. 58. The method of claim 57, comprising bonding the thermoplastic adhesive at a temperature 0-200° C. below the melting point of the perfluorocopolymer matrix.

59. 60. The method of claim 58, comprising bonding the thermoplastic adhesive at a temperature 0-50° C. below the melting point of the perfluorocopolymer matrix.

60. 57. The method of claim 56, wherein stacking the plurality of printed wiring boards comprises bonding adjacent printed wiring boards using a thermosetting adhesive.

61. 61. The method of claim 60, comprising curing the thermosetting adhesive at a temperature of from 150°C to 250°C.

62. 57. The method of claim 56, comprising defining a through hole through at least a portion of a thickness of the multi-layer laminate structure.

63. 63. The method of claim 62, comprising defining the through holes in an ultraviolet drilling process.

64. 1. A method of making a laminate article, comprising: forming a layered article, said layered article comprising: First and second polymeric films, each film comprising: a perfluorocopolymer matrix comprising a fluorinated perfluorocopolymer and a non-fluorinated perfluorocopolymer; a first and a second polymer film comprising a UV additive; a quartz cloth disposed between the first polymer film and the second polymer film; a conductive cladding disposed in contact with the first film; and applying heat and pressure to said layered article to form said laminate article.

65. 65. The method of claim 64, wherein the fluorinated perfluoro copolymer comprises a fluorinated tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymer and the non-fluorinated perfluoro copolymer comprises a non-fluorinated tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymer.

66. 65. The method of claim 64, wherein applying heat and pressure to the layered article comprises compressing the layered article within a heated platen.

67. 65. The method of claim 64, wherein applying heat and pressure to the layered article comprises processing the layered article in a roll-to-roll lamination process.

68. 65. The method of claim 64, wherein applying heat and pressure to the layered article comprises applying a temperature to the layered article that is 10-30° C. above the melting point of the perfluorocopolymer matrix.

69. 65. The method of claim 64, wherein applying heat and pressure to the layered article comprises applying a temperature of 300°C to 400°C to the layered article.

70. 65. The method of claim 64, wherein applying heat and pressure to the layered article comprises applying a pressure of between 200 psi and 1000 psi to the layered article.

71. 65. The method of claim 64, comprising forming the first film and the second film in a melt processing and extrusion process.

72. 72. The method of claim 71, wherein forming the first film and the second film comprises blending the fluorinated perfluoro copolymer and the non-fluorinated perfluoro copolymer.

73. 73. The method of claim 72, comprising dispersing an additive material in said fluorinated perfluoro copolymer prior to mixing said fluorinated perfluoro copolymer with said non-fluorinated perfluoro copolymer.

74. 65. The method of claim 64, comprising treating the quartz cloth with a fluoropolymer treatment.

75. 75. The method of claim 74, wherein treating the quartz cloth with a fluoropolymer treatment comprises coating the quartz cloth with a fluoropolymer coating.

76. 76. The method of claim 75, wherein coating the quartz cloth with a fluoropolymer coating comprises coating the quartz cloth in a solution coating process.

77. 76. The method of claim 75, wherein coating the quartz cloth with a fluoropolymer coating comprises depositing fluoropolymer particles on a surface of the quartz cloth.

78. 65. The method of claim 64, wherein each polymer film comprises a first layer comprising the fluorinated perfluoro copolymer and the non-fluorinated perfluoro copolymer, and a second layer comprising the non-fluorinated perfluoro copolymer, each second layer being disposed in contact with the quartz cloth, and each second layer being disposed in contact with the conductive cladding.